Synthesis and biological evaluation of a novel MUC1 glycopeptide conjugate vaccine candidate comprising a 4’-deoxy-4’-fluoro-Thomsen–Friedenreich epitope - Johannes, Manuel; Reindl, Maximilian; Gerlitzki, Bastian; Schmitt, Edgar; Hoffmann-Röder, Anja (Beilstein Journal of Organic Chemistry, 2015)
The development of selective anticancer vaccines that provide enhanced protection against tumor recurrence and metastasis has been the subject of intense research in the scientific community. The tumor-associated glycoprotein MUC1 represents a well-established target for cancer immunotherapy and has been used for the construction of various synthetic vaccine candidates. However, many of these vaccine prototypes suffer from an inherent low immunogenicity and are susceptible to rapid in vivo degradation. To overcome these drawbacks, novel fluorinated MUC1 glycopeptide-BSA/TTox conjugate vaccines have been prepared. Immunization of mice with the 4’F-TF-MUC1-TTox conjugate resulted in strong immune responses overriding the natural tolerance against MUC1 and producing selective IgG antibodies that are cross-reactive with native MUC1 epitopes on MCF-7 human cancer cells.
Keywords: cancer immunotherapy; fluorinated carbohydrates; glycoconjugates; MUC1; TACA